Reinforced granular fill-soft soil system: Membrane effect - Ghosh C.; Madhav M.R. (My University, 2025)
A new model for a reinforced shallow foundation bed is proposed by incorporating the 'rough membrane' element for a single layer reinforcement. Mechanics of the rough membrane element with the assumption of horizontal shear stress transfer at the soil/reinforcement interfaces are explained and formulated. The model is generalized by incorporating nonlinear responses of the soft soil and of the granular fill under plane strain loading conditions. The membrane effect is quantified in terms of the improvement in the load-settlement responses of the composite foundation system over the unreinforced one. Parametric results indicate that reinforcement while in tension spreads the load over a larger area, leading to a reduction in the settlement beneath the footing. © 1995.